Essential environment : the science behind the stories - Withgott, Jay; Laposata, Matthew (NY, NY : Pearson, 2019)
"With this volume, we aim to meet the needs of instructors who favor a more succinct and afford-able book. We have distilled the most essential content from our full-length book, Environment: The Science behind the Stories, now in its sixth edition. We have streamlined our material, updated our coverage, and carefully crafted our writing to make Essential Environment every bit as readable, informative, and engaging as its parent volume" --
Science and sustainability: an introduction to environmental science -- Environmental systems: matter, energy, and ecosystems -- Evolution, biodiversity, and population ecology -- Species interactions and community ecology -- Economics, policy, and sustainable development -- Human population -- Soil, agriculture, and the future of food -- Biodiversity and conservation biology -- Forests, forest management, and protected areas -- Environmental health and toxicology -- Geology, minerals, and mining -- Fresh water, oceans, and coasts -- Atmospheric science, air quality, and pollution control -- Global climate change.
Includes bibliographical references and index.
Keywords: Environmental sciences